Assessment of community-wide antimicrobials usage in Eastern China using wastewater-based epidemiology. (15th August 2022) - Xu, Like; Zang, Jinxin; Cong, Wenjuan; Holton, Elizabeth; Jiang, Lufang; Sheppard, Samuel K.; Wang, Yingying; Wang, Na; Weeks, Jason; Fu, Chaowei; Jiang, Qingwu; Lambert, Helen; et al.
Highlights: First application of WBE in Eastern China to assess the community-wide antimicrobials usage. Spatiotemporal trends in concentrations, daily loads and population-normalised daily loads were measured. Paired parent and metabolite analysis were included. Contribution of environmental AMR from antibiotic manufacturing was recognised. Abstract: Wastewater-based epidemiology (WBE) has potential to identify the epidemiological links between people, animals, and the environment, as part of antimicrobial resistance (AMR) surveillance. In this study, we investigated six wastewater treatment plants (WWTPs) serving six communities located in two regions in Eastern China: Site A in Zhejiang and site B in Jiangsu province to assess the public use of antimicrobial agents (AA). Fifty antimicrobials and 24 of their metabolites were quantified using ultraperformance liquid chromatography coupled with triple quadrupole tandem mass spectrometry (UPLC-MS/MS). Spatiotemporal trends were established for measured concentrations, daily loads, and population-normalised daily loads. Daily AA mass loads varied between 1.6 g/day and 324.6 g/day reflecting the WWTP scales, with macrolides and β-lactams showing the highest overall environmental burden at 223.7 g/day and 173.7 g/day, respectively. Emissions of antibiotic residues from manufacturing have been observed, with the peak daily load 12-fold higher than the overall load from a community serving a population of over 600, 000. Community exposure levels of 225.2 ± 156.2 mg/day/1000 inhabitant and 351.9 ± 133.5 mg/day/1000 inhabitant were recorded in site A and B, respectively. Paired parent-metabolites analysis identified a large proportion (64–78%) of un-metabolised metronidazole and clindamycin at site B, indicating improper disposal of unused drugs either in the community or in livestock production. Consumption levels, calculated via WBE, suggested relatively low antimicrobial usage in Eastern China compared to other areas in China. This first application of WBE in Eastern China to assess the community-wide exposure to AAs has potential to inform regional antimicrobial stewardship. Graphical abstract: Image, graphical abstract